2021
DOI: 10.3389/fpubh.2021.652998
|View full text |Cite
|
Sign up to set email alerts
|

Pick the Freshmen Up for a “Healthy Study Start” Evaluation of a Health Promoting Onboarding Program for First Year Students at the Carinthia University of Applied Sciences, Austria

Abstract: Introduction: Universities are an essential setting for creating health promoting environments. Evidence shows that university life can pose various threats to the students' health. Especially first year students are vulnerable to mental health issues. To support well-being and prevent psychological distress from the first day of studying, onboarding programs are needed to promote the students' health and their self- and social competencies. The study demonstrates a tailored multi-component onboarding interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 54 publications
1
12
0
4
Order By: Relevance
“…All three health resources were related to a lack of sleeping problems. These results support the importance of maintaining sustainable health-promoting strategies during higher education, as has been described in previous research [ 17 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All three health resources were related to a lack of sleeping problems. These results support the importance of maintaining sustainable health-promoting strategies during higher education, as has been described in previous research [ 17 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study that included an intervention using didactical approaches (e.g. peer mentoring) and team teaching among students enrolled on bachelor-level health and social work programmes reported that students in the intervention group showed significant effects on self- and social competencies compared with controls [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Der Beginn eines Studiums und der Eintritt in das Studierendenleben stellt für junge Menschen einen neuen Lebensabschnitt dar, der das bisherige Leben verändert und unbekannten Anforderungen -auch vor dem Hintergrund des veränderten Studiensystems durch die Bologna-Reform -birgt [18,19,27]. Die Absolvierung eines dualen Studiums geht für die Studienanfänger*innen zudem vom Studienstart an mit einem hohen Maß an Organisation und Struktur einher [15].…”
Section: Hintergrundunclassified
“…Studierende werden im Studium mit Unsicherheiten, stressigen Prüfungsphasen, Erfolgen und Misserfolgen konfrontiert und lernen, Verantwortung für sich selbst und ihr Tun zu übernehmen [17]. Die Studienzeit kann für junge Erwachsene eine sehr prägende Lebensphase sein [23], in der die eigene Gesundheit möglicherweise weniger im Fokus steht [17,18]. Aktuelle Studien über Studierende im Allgemeinen geben Hinweise darauf, dass die Lebensphase Studium die eigene Gesundheit und gesundheitsrelevante Verhaltensweisen beeinflussen kann [9,18,27].…”
Section: Hintergrundunclassified
“…University wellbeing courses take a variety of approaches, including mindfulness ( Hassed et al, 2009 ), mental health literacy ( Kurki et al, 2021 ), and psychoeducational life skills ( Limarutti et al, 2021 ). In this review, we focus on wellbeing courses delivered within a positive psychology framework.…”
Section: Introductionmentioning
confidence: 99%